ANTHOLOGY OF SCIENCE AND ITS IMPLICATIONS FOR THE DEVELOPMENT OF CONTEMPORARY ISLAMIC STUDIES - Ayu Aisyatun Nabila; Nurul Huda (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This research examines the ontology of knowledge from an Islamic perspective and its implications for the development of contemporary Islamic studies. Amidst modern social, cultural, and technological changes, a comprehensive and adaptive scientific approach is needed. Using a qualitative method based on literature review, this research examines three main ontological dimensions—reality, metaphysics, and the object of knowledge—based on the thinking of classical figures such as Al-Farabi, Al-Ghazali, and Ibn Khaldun, as well as contemporary thinkers Syed Muhammad Naquib al-Attas and Mohammed Arkoun. The results show that the ontology of Islamic knowledge places revelation and reason as a balanced epistemological basis. Reality is understood hierarchically within the framework of monotheism, encompassing the physical, social, and spiritual dimensions. Metaphysics serves as a link between branches of knowledge, while the object of knowledge encompasses various disciplines without a hierarchy of values. Implications for contemporary Islamic studies include eliminating the dichotomy between religious and general knowledge, contextualizing scientific methodology, responding to global humanitarian issues, and developing an inclusive epistemology. Practically, this research encourages integrative curriculum reconstruction, multidisciplinary research, and strengthening the role of Muslim intellectuals in public discourse. This research emphasizes that strengthening ontological foundations is an epistemological imperative for Islamic studies to develop holistically, integratively, and provide solutions to address the challenges of modern humanity and realize the mission of rahmatan lil 'alamin (blessing for the universe).